Characteristics of Snorkeling Tourist on Pramuka Island, Thousand Islands: Karakteristik Wisatawan Snorkeling Di Pulau Pramuka Kepulauan Seribu - Aulia Yuniar Fadillah; Rahma Wijdanisa (Politeknik Pariwisata Makassar, 2024)
The characteristics of tourists play an important role in determining the tourist destinations they want to visit. The tourism potential offered on Pramuka Island is marine and coastal tourism. Snorkeling marine tourism has become one of the most popular diving attractions on Pramuka Island because it is quite safe and affordable. The high number of snorkeling tourism visits requires an analysis to enhance marketing planning that is more specific based on tourist characteristics, aiming to predict tourist needs, so that the interests and patterns of tourists who want to go snorkeling align with the target. The research method used is a quantitative descriptive method, with the sampling technique being accidental sampling. The research findings reveal that the characteristics of tourists in choosing snorkeling tourism destinations in Pramuka Island can be examined based on factors such as age, education, occupation, income, distance, origin, and frequency of visit